2019
DOI: 10.1103/physreva.99.052704
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of p -wave three-body losses via a cascade process

Abstract: We describe the three-body loss coefficient of identical fermions with p-wave interactions using a set of rate equations in which three-body recombination happens via an indirect process. Our theoretical treatment explains experimental results just above the universal scaling law regime of weak interactions. Furthermore, we theoretically extend and experimentally verify the rate equation model for the case of atoms trapped in two dimensions. Moreover, we find that the three-body loss coefficient in a two-dimen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 66 publications
4
19
0
Order By: Relevance
“…The numerical calculation with an adiabatic hyperspherical approach predicted that α rec ∝ |v| 8/3 for R/|v| 1/3 0.1 (irrespective of the sign of v) [18]. For negative and small v where recombination leads to formation of deep dimers, α rec was found to be consistent with |v| 8/3 -scaling based on the numerically solved Faddeev integral equation [19], and is also consistent with the recent experiments [20][21][22] in the same parameter regime. However, an analytic calculation based on a two-channel model pointed out that α rec ∝ v 5/2 R 1/2 for recombina-tions into shallow dimers at v > 0 [23].…”
supporting
confidence: 85%
“…The numerical calculation with an adiabatic hyperspherical approach predicted that α rec ∝ |v| 8/3 for R/|v| 1/3 0.1 (irrespective of the sign of v) [18]. For negative and small v where recombination leads to formation of deep dimers, α rec was found to be consistent with |v| 8/3 -scaling based on the numerically solved Faddeev integral equation [19], and is also consistent with the recent experiments [20][21][22] in the same parameter regime. However, an analytic calculation based on a two-channel model pointed out that α rec ∝ v 5/2 R 1/2 for recombina-tions into shallow dimers at v > 0 [23].…”
supporting
confidence: 85%
“…On the other hand, the validity of the effective Hamiltonian [Eq. (34)] is not guaranteed in the BCS side a −1 < 0. The density dependence of D and µ in the BCS side is given by…”
Section: B Low-energy Effective Model For the Majorana Zero Mode At T...mentioning
confidence: 99%
“…Regarding the realization of topological superfluids in ultracold atomic gases, a p-wave superfluid Fermi gas has been one of the promising candidates for the past few decades [25][26][27] . However, various effects such as threebody loss and dipolar relaxation [28][29][30][31][32][33][34] prevent the systems from reaching the superfluid state. At the same time, it has recently been suggested that such atom loss processes may be suppressed in the low-dimensional systems [35][36][37][38] .…”
Section: Introductionmentioning
confidence: 99%
“…Our main interest in the present study is in generalizing our understanding of such systems having a very large p-wave scattering volume. This interest has been sparked in part by recent experiments relating to the three-body loss rate and the unitary limit of spinpolarized Fermi gases [12][13][14], as well as theoretical investigations that have predicted and analyzed the mechanisms of recombination or loss in a single-component fermion system [15][16][17][18]. There are also now multiple ways of controlling ultracold atom-atom interactions, via not only magnetic Fano-Feshbach resonances, but also lightinduced or rf-induced resonances or orbital resonances; these experimental tools can in principle be used to independently modify both s-wave and p-wave interactions in a few-body system [19][20][21].…”
Section: Introductionmentioning
confidence: 99%